Selection of Endophytic Bacteria from Root of Okra (Abelmoschus esculantus) as a Biocontrol of Fusarium oxysporum - Evan Purnama Ramdan; Ely Lailatul Maghfiroh; Reni Rinika; Abdul Munif (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2021)
Okra has become one of the most important vegetables in Indonesia, in which its production need to be increased. One limiting factor is the attack ofsoil-borne pathogens that are difficult to control. Therefore, new alternative controls need to be assessed. In this research, several endophytic bacteria wereisolated and tested for their potency as control of Fusarium oxysporum. Isolation of endophytic bacteria was derived from roots of okra plants which were then characterized by morphospecies and tested for their safety by haemolysis and hypersensitivity tests. A dual culture test was performed to obtain endophytic bacteria that have potential as biocontrol agents by observing formation of inhibitory zones. In addition, inhibitory properties of endophytic bacteria were also calculated. The results showed that nine isolates of endophytic bacteria were obtained from okra roots. Selection by haemolysis and hypersensitivity tests showed that there were three isolates that were biologically safe. In further testing, one of the three obtained isolates (AOB3) was considered the best in inhibit F. oxysporum growth with an efficacy of 19.3%, and form an inhibitory zone as a characteristic of antibiotic mechanism.